Let it go : downsizing your way to a richer, happier life - Walsh, Peter, 1956- (Rodale, 2017)
"Whether you are selling your family home, blending households into a new home, or cleaning out your aging parents' home, sorting through a lifetime's worth of accumulated possessions can be a daunting and stressful experience. Decluttering guru Peter Walsh recently went through the process of downsizing his childhood home and dividing his late parents' family possessions. He realized that making these decisions about mementos and heirlooms creates strong emotions and can be an overwhelming chore. In Let It Go, Peter will help you turn downsizing into a rejuvenating life change with his useful tips and practical takeaways,"--Amazon.com.